2015
DOI: 10.1016/j.psyneuen.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Opioid partial agonist buprenorphine dampens responses to psychosocial stress in humans

Abstract: Preclinical and clinical evidence indicates that opioid drugs have stress-dampening effects. In animal models, opioid analgesics attenuate responses to isolation distress, and in humans, opioids reduce stress related to anticipation of physical pain. The stress-reducing effects of opioid drugs may contribute to their abuse potential. Despite this evidence in laboratory animals, the effects of opioids on responses to psychosocial stress have not been determined in humans. Here we examined the effects of bupreno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 39 publications
8
60
2
3
Order By: Relevance
“…Therefore, it is a suitable treatment choice for refractory depression, anxiety, self-injurious behaviors, and suicidal ideation (6,7,(14)(15)(16)(17). In the present report, we observed that 8 mg of buprenorphine had a rapid effect on the reduction and cessation of suicidal thoughts and depression.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Therefore, it is a suitable treatment choice for refractory depression, anxiety, self-injurious behaviors, and suicidal ideation (6,7,(14)(15)(16)(17). In the present report, we observed that 8 mg of buprenorphine had a rapid effect on the reduction and cessation of suicidal thoughts and depression.…”
Section: Discussionsupporting
confidence: 53%
“…Previously, Striebel and Yovell indicated the antisuicidal potential of low-dose buprenorphine administration in a limited period (6,7). Overall, buprenorphine reduces physiological and subjective responses to social stressors, including social rejection (14). In this regard, Karp et al demonstrated the effectiveness of lowdose buprenorphine for treatment-resistant depression in older adults (17).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with theorizing, buprenorphine, which stimulates opioids, increased satisfaction with performance to a social stressor (giving a speech; Bershad, Jaffe, Childs, & de Wit, 2015, 2015 and reduced sensitivity to recognizing negative facial expressions (fear; Ipser et al, 2013). OPIOIDS AND SOCIAL CONNECTION 8 However, other findings show inconsistent results.…”
Section: Opioids and Negative Social Experiencesmentioning
confidence: 75%
“…The distance of the slash marks (in centimeters) from the beginning of the line is used to create a numerical value, where a greater number of centimeters indicate the higher levels of stress perception (Aitken, 1969;Bond and Lader, 1974;Hellhammer and Schubert, 2012;Creswell et al, 2014). The POMS questionnaire is developed at 6 points and the questionnaire consists of 72 adjectives, comprising eight subscales: anxiety, dejection, hostility, vigor, fatigue, confusion, friendliness, and elation (McNair et al, 1971;Bershad et al, 2015).…”
Section: Behavioral Assessmentmentioning
confidence: 99%